The analysis of student’ difficulties in mastering static fluid concept - Tsania Nur Diyana; Sutopo Sutopo; Sunaryono Sunaryono (Universitas PGRI Kanjuruhan Malang, 2020)
This study aimed to analyze the difficulties experienced by students in mastering Static Fluid concept. This study used descriptive quantitative method with 48 students of Physics Education Department. The instrument of this research was 13 reasoned-multiple choice questions. According to the results, although there was an improvement, most students were difficult to understand certain concepts. This research revelaed some difficulties experienced by students on static fluid concept. Among others are students failed to portray the forces that worked on certain object in fluid, then as a result, they failed to determine the ratio of pressure. In addition, the students were difficult to determine the changing of water pressure on the closed vessel based on the main law of hydrostatics and Pascal’s Law.